Os “Braga da Pontezinha”: os mutirões como encontros que reafirmam pertencimentos ao lugar e à família - Moura, Veralúcia Pimenta de (2020)
The text of this dissertation begins with a description of my own experience, since I have lived for 20 years in Pontezinha, a rural area inside the town of ​​Santo Antônio do Descoberto, state of Goiás - Brazil, where the research was carried out. In order to talk about my “affection” for Braga da Pontezinha and also my interest in developing this paper, the studies of Marilyn Strathern and Jeanne Favret-Saada helped me to live this “ethnographic experience” considering the concepts of “immersion in the field” (STRATHERN, 2014) and “to be affected” (FAVRET-SAADA, 2005). Inspired by these authors, the narratives of the interlocutors were gathered in the scope of the research and the trajectory of the people from slave laborers in the gold mines of Santa Luzia in the first half of the 19th century until their arrival at Pontezinha. It is on the banks of the Córrego Fundo that the site “Os Braga” first appears. Taking into account the indications of ethnography, I reintroduce its citizens, as since after the Corumbá IV Dam in 2006, they started to be recognized by the municipality and by the Concessionaire as a “traditional community”. The CORPO formal association, since 1988, is presented from the perspective of the lack of water issue and from its conflicts with the Community. On the trail of the ethnographic reports, I reformulate the research question and reflect about the “mutirões” in the current scenario as a form of resistance from Braga to several interferences, in order to preserve the unity of the family and of the place. Final considerations allow to highlight some similarities between quilombos and “mutirões” then make a comparison between them with the habitus (BOURDIEU, 2010) and the “campesinidade” (WOORTMANN, 1990).